Digital health in clinical pharmacy practice: transforming precision medicine and pharmacometrics in Africa - Sumaiah J. Alarfaj; Engy Wahsh; Khaled Saad; Eman S. Sawan (Frontiers in Pharmacology, 2026)
African nations still struggle with several healthcare challenges such as high prevalence of communicable and non-communicable diseases, underdeveloped healthcare systems, lack of healthcare personnel, and uneven distribution of quality healthcare services. Resource constraints and a fragmented healthcare system make the aforementioned challenges even more difficult to solve. However, digital health technology and artificial intelligence (AI) can be viewed as revolutionary instruments that may help to overcome the mentioned challenges and enhance healthcare practices in Africa. The present article provides a review of how digital health technologies and AI influence clinical pharmacy practice and contribute to precision medicine and pharmacometrics in African nations. To do that, a literature search has been performed using the PubMed, Scopus, and Web of Science electronic databases for relevant articles about digital health, AI, clinical pharmacy, precision medicine, pharmacometrics, and healthcare delivery in Africa. Healthcare technologies, such as telemedicine, mobile health apps, electronic health records, and clinical decision support systems powered by AI, are becoming more pervasive and widening the scope of work for clinical pharmacists through their contribution to medication optimization, therapeutic monitoring, and evidence-based clinical decision-making. Their application within precision medicine allows creating an individual treatment strategy considering the genetic and clinical features of the patients. At the same time, pharmacometric approaches, especially pharmacokinetics and pharmacodynamics modeling and model-informed precision dosing, help to optimize drug prescription and therapy outcomes for different African populations. The present article provides a review of how integrating digital health technologies and AI into clinical pharmacy practice could be a promising approach for enhancing precision medicine in Africa. The review also explores their implementation challenges and future opportunities for reasonable healthcare delivery.